GNAQ mutations drive port wine birthmark-associated Sturge-Weber syndrome: A review of pathobiology, therapies, and current models - Van Trigt, William K.; Kelly, Kristen M.; Hughes, Christopher C. W. (Frontiers in Human Neuroscience, 2022)
Port-wine birthmarks (PWBs) are caused by somatic, mosaic mutations in the G protein guanine nucleotide binding protein alpha subunit q (GNAQ) and are characterized by the formation of dilated, dysfunctional blood vessels in the dermis, eyes, and/or brain. Cutaneous PWBs can be treated by current dermatologic therapy, like laser intervention, to lighten the lesions and diminish nodules that occur in the lesion. Involvement of the eyes and/or brain can result in serious complications and this variation is termed Sturge-Weber syndrome (SWS). Some of the biggest hurdles preventing development of new therapeutics are unanswered questions regarding disease biology and lack of models for drug screening. In this review, we discuss the current understanding of GNAQ signaling, the standard of care for patients, overlap with other GNAQ-associated or phenotypically similar diseases, as well as deficiencies in current in vivo and in vitro vascular malformation models.